Littoral‐zone influences on particulate organic matter composition along the freshwater‐tidal Hudson River, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2012)
A multi‐tracer approach was applied to particulate organic material (POM) biogeochemistry along a 165‐km transect of the freshwater‐tidal portion of the Hudson River estuary (HRE). Elemental carbon and nitrogen, stable isotopes, chlorophyll a , and lignin phenols were measured monthly at a mid‐estuary station from August to November 2007, and monthly at the same station and 3–5 additional stations in 2008. POM at stations proximal to major tidal wetland and aquatic vegetation (WETAV) zones showed ∼ 2‰ higher carbon isotopic signature of particulate organic carbon ( δ 13 C POC ), ∼ 3‰ higher nitrogen isotopic signature of particulate nitrogen ( δ 15 N PN ), elevated chlorophyll a levels, and up to 3‐fold increases in Λ 8 ‐lignin phenols indicative of relatively fresh plant matter. This prominent shift in POM composition suggests that WETAV areas supply compositionally unique organic matter along the HRE, especially during low flow. Based on shifts in geochemical tracers downstream of the largest WETAV zone, this POM appears to be readily incorporated, metabolized, and/or deposited to bed sediments. Despite representing